Proposed Marketing Strategy For Haznet - Harnawan, Willy; Purwanegara, Mustika Sufiati (The Indonesian Journal of Business Administration, 2015)
Abstract – Internet has become a human need that cannot be used of pleasure purpose such as online game. As an entrepreneur, Mr. Harlianda saw a business opportunity by establishing HARZnet in 2011. Located in strategic location, in Dago area, HARZnet couldn’t meet the target instead of suffer a declining on sales. Those two business issues will be analysed by distributing 100 questionnaires, 4C 6P, SWOT analysis, and STP. From marketing point of view, the first solution that needs to be done is to make clear STP that leads to clearer marketing mix and strategy. After that, HARZnet needs to change its’ perception in order to attract and maintain customers. Finally, new marketing mix is proposed. For solution implementation, the author has made simple budgeting and timeline.Keywords: marketing, sales, game